2017
DOI: 10.1111/cas.13386
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activity of sorafenib and betulinic acid against clonogenic activity of non‐small cell lung cancer cells

Abstract: The highly selective multi‐targeted agent sorafenib is an inhibitor of a number of intracellular signaling kinases with anti‐proliferative, anti‐angiogenic and pro‐apoptotic effects in various types of tumors, including human non‐small cell lung cancer (NSCLC). Betulin displays a broad spectrum of biological and pharmacological properties, including anticancer and chemopreventive activity. Combination of drugs with different targets is a logical approach to overcome multilevel cross‐stimulation among key signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 55 publications
2
16
0
1
Order By: Relevance
“…Recently, we have shown that combination treatment with SOR and BA caused significant proliferation-inhibitory effects in NSCLC cell lines [ 6 ]. We first investigated the effects of SOR and BA on cell viability using the MTS assay to determine whether their combination can inhibit the proliferation of human PDAC cell lines with different mutational KRAS status ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have shown that combination treatment with SOR and BA caused significant proliferation-inhibitory effects in NSCLC cell lines [ 6 ]. We first investigated the effects of SOR and BA on cell viability using the MTS assay to determine whether their combination can inhibit the proliferation of human PDAC cell lines with different mutational KRAS status ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Combination treatment with SOR and BA markedly decreased the colony-forming capability of PDAC cells. This treatment has been shown previously to be nontoxic for normal human peripheral blood lymphocytes [ 6 ]. It should be noted that tumor cell cloning efficiency is positively correlated with proliferation and self-renewal abilities, which may be associated with cell tumorigenesis [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Favourable results were obtained by combining BA and, respectively, vincristine, 5-fluorouracil, doxorubicin, etoposide, actinomycin D, mithramycin A, cisplatin, taxol, oxaliplatin, or irinotecan, as well as ionizing radiation (Sawada et al 2004;Jung et al 2007;Gao et al 2011;Bache et al 2011;Zhao et al 2012;Csuk 2014). In turn, a combination of BE and sorafenib, a kinase inhibitor effective against various carcinomas, enhanced the induction of apoptosis in different non-small cell lung cancer lines (Kutkowska et al 2017).…”
Section: Anti-tumoral Activity Of Be and Bamentioning
confidence: 99%
“…The assay was performed according to the method described earlier . After seeding at a density of 4 × 10 4 cells/well in a 24‐well plate (TPP, Trasadingen, Switzerland) and attaching overnight, the cells were incubated for 24 hours in medium alone or with Pt‐TCEP in the final concentration of 2 or 3 μM.…”
Section: Methodsmentioning
confidence: 99%